Linear Algebra Examples
(2,0,1)(2,0,1) , (-2,1,1)(−2,1,1)
Step 1
Use the cross product formula to find the angle between two vectors.
θ=arcsin(|a⃗×b⃗||a⃗||b⃗|)θ=arcsin(|a⃗×b⃗||a⃗||b⃗|)
Step 2
Step 2.1
The cross product of two vectors a⃗a⃗ and b⃗b⃗ can be written as a determinant with the standard unit vectors from ℝ3 and the elements of the given vectors.
a⃗×b⃗=a⃗×b⃗=|îĵk̂a1a2a3b1b2b3|
Step 2.2
Set up the determinant with the given values.
a⃗×b⃗=|îĵk̂201-211|
Step 2.3
Choose the row or column with the most 0 elements. If there are no 0 elements choose any row or column. Multiply every element in row 1 by its cofactor and add.
Step 2.3.1
Consider the corresponding sign chart.
|+-+-+-+-+|
Step 2.3.2
The cofactor is the minor with the sign changed if the indices match a - position on the sign chart.
Step 2.3.3
The minor for a11 is the determinant with row 1 and column 1 deleted.
|0111|
Step 2.3.4
Multiply element a11 by its cofactor.
|0111|î
Step 2.3.5
The minor for a12 is the determinant with row 1 and column 2 deleted.
|21-21|
Step 2.3.6
Multiply element a12 by its cofactor.
-|21-21|ĵ
Step 2.3.7
The minor for a13 is the determinant with row 1 and column 3 deleted.
|20-21|
Step 2.3.8
Multiply element a13 by its cofactor.
|20-21|k̂
Step 2.3.9
Add the terms together.
a⃗×b⃗=|0111|î-|21-21|ĵ+|20-21|k̂
a⃗×b⃗=|0111|î-|21-21|ĵ+|20-21|k̂
Step 2.4
Evaluate |0111|.
Step 2.4.1
The determinant of a 2×2 matrix can be found using the formula |abcd|=ad-cb.
a⃗×b⃗=(0⋅1-1⋅1)î-|21-21|ĵ+|20-21|k̂
Step 2.4.2
Simplify the determinant.
Step 2.4.2.1
Simplify each term.
Step 2.4.2.1.1
Multiply 0 by 1.
a⃗×b⃗=(0-1⋅1)î-|21-21|ĵ+|20-21|k̂
Step 2.4.2.1.2
Multiply -1 by 1.
a⃗×b⃗=(0-1)î-|21-21|ĵ+|20-21|k̂
a⃗×b⃗=(0-1)î-|21-21|ĵ+|20-21|k̂
Step 2.4.2.2
Subtract 1 from 0.
a⃗×b⃗=-î-|21-21|ĵ+|20-21|k̂
a⃗×b⃗=-î-|21-21|ĵ+|20-21|k̂
a⃗×b⃗=-î-|21-21|ĵ+|20-21|k̂
Step 2.5
Evaluate |21-21|.
Step 2.5.1
The determinant of a 2×2 matrix can be found using the formula |abcd|=ad-cb.
a⃗×b⃗=-î-(2⋅1-(-2⋅1))ĵ+|20-21|k̂
Step 2.5.2
Simplify the determinant.
Step 2.5.2.1
Simplify each term.
Step 2.5.2.1.1
Multiply 2 by 1.
a⃗×b⃗=-î-(2-(-2⋅1))ĵ+|20-21|k̂
Step 2.5.2.1.2
Multiply -(-2⋅1).
Step 2.5.2.1.2.1
Multiply -2 by 1.
a⃗×b⃗=-î-(2--2)ĵ+|20-21|k̂
Step 2.5.2.1.2.2
Multiply -1 by -2.
a⃗×b⃗=-î-(2+2)ĵ+|20-21|k̂
a⃗×b⃗=-î-(2+2)ĵ+|20-21|k̂
a⃗×b⃗=-î-(2+2)ĵ+|20-21|k̂
Step 2.5.2.2
Add 2 and 2.
a⃗×b⃗=-î-1⋅4ĵ+|20-21|k̂
a⃗×b⃗=-î-1⋅4ĵ+|20-21|k̂
a⃗×b⃗=-î-1⋅4ĵ+|20-21|k̂
Step 2.6
Evaluate |20-21|.
Step 2.6.1
The determinant of a 2×2 matrix can be found using the formula |abcd|=ad-cb.
a⃗×b⃗=-î-1⋅4ĵ+(2⋅1-(-2⋅0))k̂
Step 2.6.2
Simplify the determinant.
Step 2.6.2.1
Simplify each term.
Step 2.6.2.1.1
Multiply 2 by 1.
a⃗×b⃗=-î-1⋅4ĵ+(2-(-2⋅0))k̂
Step 2.6.2.1.2
Multiply -(-2⋅0).
Step 2.6.2.1.2.1
Multiply -2 by 0.
a⃗×b⃗=-î-1⋅4ĵ+(2-0)k̂
Step 2.6.2.1.2.2
Multiply -1 by 0.
a⃗×b⃗=-î-1⋅4ĵ+(2+0)k̂
a⃗×b⃗=-î-1⋅4ĵ+(2+0)k̂
a⃗×b⃗=-î-1⋅4ĵ+(2+0)k̂
Step 2.6.2.2
Add 2 and 0.
a⃗×b⃗=-î-1⋅4ĵ+2k̂
a⃗×b⃗=-î-1⋅4ĵ+2k̂
a⃗×b⃗=-î-1⋅4ĵ+2k̂
Step 2.7
Multiply -1 by 4.
a⃗×b⃗=-î-4ĵ+2k̂
Step 2.8
Rewrite the answer.
a⃗×b⃗=(-1,-4,2)
a⃗×b⃗=(-1,-4,2)
Step 3
Step 3.1
The norm is the square root of the sum of squares of each element in the vector.
|a⃗×b⃗|=√(-1)2+(-4)2+22
Step 3.2
Simplify.
Step 3.2.1
Raise -1 to the power of 2.
|a⃗×b⃗|=√1+(-4)2+22
Step 3.2.2
Raise -4 to the power of 2.
|a⃗×b⃗|=√1+16+22
Step 3.2.3
Raise 2 to the power of 2.
|a⃗×b⃗|=√1+16+4
Step 3.2.4
Add 1 and 16.
|a⃗×b⃗|=√17+4
Step 3.2.5
Add 17 and 4.
|a⃗×b⃗|=√21
|a⃗×b⃗|=√21
|a⃗×b⃗|=√21
Step 4
Step 4.1
The norm is the square root of the sum of squares of each element in the vector.
|a⃗|=√22+02+12
Step 4.2
Simplify.
Step 4.2.1
Raise 2 to the power of 2.
|a⃗|=√4+02+12
Step 4.2.2
Raising 0 to any positive power yields 0.
|a⃗|=√4+0+12
Step 4.2.3
One to any power is one.
|a⃗|=√4+0+1
Step 4.2.4
Add 4 and 0.
|a⃗|=√4+1
Step 4.2.5
Add 4 and 1.
|a⃗|=√5
|a⃗|=√5
|a⃗|=√5
Step 5
Step 5.1
The norm is the square root of the sum of squares of each element in the vector.
|b⃗|=√(-2)2+12+12
Step 5.2
Simplify.
Step 5.2.1
Raise -2 to the power of 2.
|b⃗|=√4+12+12
Step 5.2.2
One to any power is one.
|b⃗|=√4+1+12
Step 5.2.3
One to any power is one.
|b⃗|=√4+1+1
Step 5.2.4
Add 4 and 1.
|b⃗|=√5+1
Step 5.2.5
Add 5 and 1.
|b⃗|=√6
|b⃗|=√6
|b⃗|=√6
Step 6
Substitute the values into the formula.
θ=arcsin(√21√5√6)
Step 7
Step 7.1
Combine √21 and √6 into a single radical.
θ=arcsin(√216√5)
Step 7.2
Cancel the common factor of 21 and 6.
Step 7.2.1
Factor 3 out of 21.
θ=arcsin(√3(7)6√5)
Step 7.2.2
Cancel the common factors.
Step 7.2.2.1
Factor 3 out of 6.
θ=arcsin(√3⋅73⋅2√5)
Step 7.2.2.2
Cancel the common factor.
θ=arcsin(√3⋅73⋅2√5)
Step 7.2.2.3
Rewrite the expression.
θ=arcsin(√72√5)
θ=arcsin(√72√5)
θ=arcsin(√72√5)
Step 7.3
Simplify the numerator.
Step 7.3.1
Rewrite √72 as √7√2.
θ=arcsin(√7√2√5)
Step 7.3.2
Multiply √7√2 by √2√2.
θ=arcsin(√7√2⋅√2√2√5)
Step 7.3.3
Combine and simplify the denominator.
Step 7.3.3.1
Multiply √7√2 by √2√2.
θ=arcsin(√7√2√2√2√5)
Step 7.3.3.2
Raise √2 to the power of 1.
θ=arcsin(√7√2√21√2√5)
Step 7.3.3.3
Raise √2 to the power of 1.
θ=arcsin(√7√2√21√21√5)
Step 7.3.3.4
Use the power rule aman=am+n to combine exponents.
θ=arcsin(√7√2√21+1√5)
Step 7.3.3.5
Add 1 and 1.
θ=arcsin(√7√2√22√5)
Step 7.3.3.6
Rewrite √22 as 2.
Step 7.3.3.6.1
Use n√ax=axn to rewrite √2 as 212.
θ=arcsin(√7√2(212)2√5)
Step 7.3.3.6.2
Apply the power rule and multiply exponents, (am)n=amn.
θ=arcsin(√7√2212⋅2√5)
Step 7.3.3.6.3
Combine 12 and 2.
θ=arcsin(√7√2222√5)
Step 7.3.3.6.4
Cancel the common factor of 2.
Step 7.3.3.6.4.1
Cancel the common factor.
θ=arcsin(√7√2222√5)
Step 7.3.3.6.4.2
Rewrite the expression.
θ=arcsin(√7√221√5)
θ=arcsin(√7√221√5)
Step 7.3.3.6.5
Evaluate the exponent.
θ=arcsin(√7√22√5)
θ=arcsin(√7√22√5)
θ=arcsin(√7√22√5)
Step 7.3.4
Simplify the numerator.
Step 7.3.4.1
Combine using the product rule for radicals.
θ=arcsin(√7⋅22√5)
Step 7.3.4.2
Multiply 7 by 2.
θ=arcsin(√142√5)
θ=arcsin(√142√5)
θ=arcsin(√142√5)
Step 7.4
Multiply the numerator by the reciprocal of the denominator.
θ=arcsin(√142⋅1√5)
Step 7.5
Multiply 1√5 by √5√5.
θ=arcsin(√142(1√5⋅√5√5))
Step 7.6
Combine and simplify the denominator.
Step 7.6.1
Multiply 1√5 by √5√5.
θ=arcsin(√142⋅√5√5√5)
Step 7.6.2
Raise √5 to the power of 1.
θ=arcsin(√142⋅√5√51√5)
Step 7.6.3
Raise √5 to the power of 1.
θ=arcsin(√142⋅√5√51√51)
Step 7.6.4
Use the power rule aman=am+n to combine exponents.
θ=arcsin(√142⋅√5√51+1)
Step 7.6.5
Add 1 and 1.
θ=arcsin(√142⋅√5√52)
Step 7.6.6
Rewrite √52 as 5.
Step 7.6.6.1
Use n√ax=axn to rewrite √5 as 512.
θ=arcsin(√142⋅√5(512)2)
Step 7.6.6.2
Apply the power rule and multiply exponents, (am)n=amn.
θ=arcsin(√142⋅√5512⋅2)
Step 7.6.6.3
Combine 12 and 2.
θ=arcsin(√142⋅√5522)
Step 7.6.6.4
Cancel the common factor of 2.
Step 7.6.6.4.1
Cancel the common factor.
θ=arcsin(√142⋅√5522)
Step 7.6.6.4.2
Rewrite the expression.
θ=arcsin(√142⋅√551)
θ=arcsin(√142⋅√551)
Step 7.6.6.5
Evaluate the exponent.
θ=arcsin(√142⋅√55)
θ=arcsin(√142⋅√55)
θ=arcsin(√142⋅√55)
Step 7.7
Multiply √142⋅√55.
Step 7.7.1
Multiply √142 by √55.
θ=arcsin(√14√52⋅5)
Step 7.7.2
Combine using the product rule for radicals.
θ=arcsin(√14⋅52⋅5)
Step 7.7.3
Multiply 14 by 5.
θ=arcsin(√702⋅5)
Step 7.7.4
Multiply 2 by 5.
θ=arcsin(√7010)
θ=arcsin(√7010)
Step 7.8
Evaluate arcsin(√7010).
θ=56.78908923
θ=56.78908923